THE DETECTION OF PHZS AND PHZM GENES IN PYOCYANIN FORMING AND ANTIBIOTIC RESISTING PSEUDOMONAS AERUGINOSA CLINICAL ISOLATES - Falah , F. Q.; Alsalim, H. A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to detect the phzS and phzM genes in Pseudomonas aeruginosa clinical isolates that form pyocyanin and resist antibiotics. The study was conducted by collecting 240 samples from different clinical sources (burns, wounds, urinary tract, and ear infections) at Medicine City laboratories Baghdad-Iraq. Only 140 samples were diagnosed as P. aeruginosa, with the major identification depending on morphological characteristics, biochemical tests, the Vitek 2 compact system, and molecular detection of the 16S rRNA gene responsible for this bacterium. Identified isolates were investigated for hemolysin, protease enzymes, and pyocyanin production. The genes phzS and phzM, involved in pyocyanin production, were investigated, and the isolates' sensitivity to 12 antibiotics was also tested. The results showed that all the isolates were able to produce hemolysin, 80% of the isolates were protease enzyme producers, and 72.15% produced pyocyanin. The presence percentage of the phzS gene (90%) was higher than that of the phzM gene (70%), and only the isolates that possessed the two genes producing pyocyanin, while those that contained one of the genes phzS or phzM did not. The highest levels of antibiotic resistance were for colistin (100%) and ceftazidime (97.14%), while the least were for imipenem (26.42%) and piperacillin-tazobactam (22.85%). The isolates producing pyocyanin are more resistant to antibiotics than those unable to produce it.